Constructing ultraporous covalent organic fameworks in seconds via an organic terracotta process - Karak, S.; Kandambeth, S.; Biswal, B. P.; Sasmal, H. S.; Kumar, S.; Pachfule, P.; Banerjee, R. (Journal of the American Chemical Society, 2017)
Research on covalent organic frameworks (COFs) has recently gathered significant momentum by the virtue of their predictive design, controllable porosity, and long-range ordering. However, the lack of solvent-free and easy-to-perform synthesis processes appears to be the bottleneck toward their greener fabrication, thereby limiting their possible potential applications. To alleviate such shortcomings, we demonstrate a simple route toward the rapid synthesis of highly crystalline and ultraporous COFs in seconds using a novel salt-mediated crystallization approach. A high degree of synthetic control in interlayer stacking and layer planarity renders an ordered network with a surface area as high as 3000 m(2) g-(1). Further, this approach has been extrapolated for the continuous synthesis of COFs by means of a twin screw extruder and in situ processes of COFs into different shapes mimicking the ancient terracotta process. Finally, the regular COF beads are shown to outperform the leading zeolites in water sorption performance, with notably facile regeneration ability and structural integrity.

Molecular level control of the capacitance of two-dimensional covalent organic frameworks: role of hydrogen bonding in energy storage materials - Chandra, S.; Chowdhury, D.R; Addicoat, M.; Heine, T.; Paul, A.; Banerjee, R. (Chemistry of Materials, 2017)
Two-dimensional redox-active covalent organic frameworks (COFs) are ideal materials for energy storage applications due to their high surface area, extended pi conjugated structure, tunable pore size, and adjustable functionalities. Herein, we report the synthesis and super capacitor application of two redox active COFs [TpPa-(OH)(2) and TpBD-(OH)(2)] along with the role of their redox active functional groups for the enrichment of specific capacitance. Of these COFs, TpPa-(OH)2 exhibited the highest specific capacitance of 416 F g(-1) at 0.5 A g(-1) current density in three electrode configuration while the highest specific capacitance was 214 F g(-1) at 0.2 A g(-1) current density in two electrode configuration. Superior specific capacitance was due to emergence of excellent pseudocapacitance by virtue of precise molecular level control over redox functionalities present in the COF backbone. This COF also demonstrated 66% capacitance retention after 10 000 cycles along with 43% accessibility of the redox-active hydroquinone (H2Q) moieties in three electrode configuration while the capacitance retention was 88% after 10 000 cycles in two electrode configuration. Exceptionally high specific capacitance of TpPa-(OH)(2) was due to the reversible proton-coupled electron transfer (2H(+)/2(e-)) of hydroquinone/benzoquinone (H(2)Q/Q) moieties wherein H(2)Q and Qhad comparable chemical stabilities during redox cycling that originated from H-bonding, which was supported by calculated structures.

Odd-even alternation in tautomeric porous organic cages with eceptional chemical stability - Bera, S.; Basu, A.; Tothadi, S.; Garai, B.; Banerjee, S.; Vanka, K.; Banerjee, R. (Angewandte Chemie-International Edition, 2017)
Amine-linked (C-NH) porous organic cages (POCs) are preferred over the imine-linked (C= N) POCs owing to their enhanced chemical stability. In general, aminelinked cages, obtained by the reduction of corresponding imines, are not shape-persistent in the crystalline form. Moreover, they require multistep synthesis. Herein, a one-pot synthesis of four new amine-linked organic cages by the reaction of 1,3,5-triformylphloroglucinol (Tp) with different analogues of alkanediamine is reported. The POCs resulting from the odd diamine (having an odd number of -CH2 groups) is conformationally eclipsed, while the POCs constructed from even diamines adopt a gauche conformation. This odd-even alternation in the conformation of POCs has been supported by computational calculations. The synthetic strategy hinges on the concept of Schiff base condensation reaction followed by keto-enol tautomerization. This mechanism is the key for the exceptional chemical stability of cages and facilitates their resistance towards acids and bases.

Selective molecular separation by interfacially crystallized covalent organic framework thin films - Dey, K.; Das, A; Mukherjee, R.; Kharul, U. K.; Banerjee, R. (Journal of the American Chemical Society, 2017)
Exponential interest in the field of covalent organic frameworks (COFs) stems from the direct correlation between their modular design principle and various interesting properties. However, existing synthetic approaches to realize this goal mainly result in insoluble and unprocessable powders, which severely restrict their widespread applicability. Therefore, developing a methodology for easy fabrication of these materials remains an alluring goal and a much desired objective. Herein, we have demonstrated a bottom-up interfacial crystallization strategy to fabricate these microcrystalline powders as large-scale thin films under ambient conditions. This unique design principle exploits liquid-liquid interface as a platform, allowing simultaneous control over crystallization and morphology of the framework structure. The thin films are grown without any support in free-standing form and can be transferred onto any desirable substrate. The porous (with Tp-Bpy showing highest SBET of 1a151 m2 g-1) and crystalline thin films, having high chemical as well as thermal stability, also hold the merit to tune the thickness as low as sub-100 nm. These nanostructured thin COF films demonstrate remarkable solvent-permeance and solute-rejection performance. A prominent instance is the Tp-Bpy thin film, which displays an unprecedented acetonitrile permeance of 339 L m-2 h-1 bar-1.

Selective molecular sieving in self-Standing porous covalent-Organic-framework membranes - Kandambeth, S.; Biswal, B. P.; Chaudhari, H. D.; Rout, K. C.; Kunjattu, H. S.; Mitra, S.; Karak, S.; Das, A.; Mukherjee, R.; Kharul, U. K.; Banerjee, R. (Advanced Materials, 2017)
Self-standing, flexible, continuous, and crack-free covalent-organic-framework membranes (COMs) are fabricated via a simple, scalable, and highly cost-effective methodology. The COMs show long-term durability, recyclability, and retain their structural integrity in water, organic solvents, and mineral acids. COMs are successfully used in challenging separation applications and recovery of valuable active pharmaceutical ingredients from organic solvents.

Syntheses and single crystal X-ray diffraction studies of hydroxynicotinic acid based complexes involving supramolecular interactions - Singh, S.K. (Polyhedron, 2017)
Aqua-bridged coordination polymers of Cu(II) and Cd(II) and a mononuclear complex of Cu(II) were solvothermally synthesized with hydroxy-decorated ligands such as 2-hydroxynicotinic acid (2-OHNAH) and 6-hydroxynicotinic acid (6-OHNAH) in aqueous-nonaqueous mixed media. All these complexes were characterized by elemental analyses (C, H, N), FT-IR, thermogravimetric analysis (TGA), powder XRD and single crystal X-ray crystallography. They are formulated as [Cu(2-OHNA)2] 1, [Cu(6-OHNA)2(μ-H2O)2]n 2 and [Cd(6-OHNA)2(μ-H2O)2]n 3. Complex 1 is mononuclear 0D square planar complex which extends its dimensionality by weak supramolecular interactions such as π–π stacking interactions and intermolecular hydrogen bonding. Complexes 2 and 3 are polymeric aqua-bridged 1D infinite chain of Cu(II) and Cd(II), respectively. The central metal ions in these two complexes are in octahedral coordination environment. These two complexes are also assembled by π–π stacking interactions, inter- and intramolecular hydrogen bonding interactions.
Keywords: 2-Hydroxynicotinic Acid; 6-Hydroxynicotinic Acid; Coordination polymer; Polymeric Aqua-Bridged; X-ray diffraction

Covalent organic frameworks: chemistry beyond the structure - Kandambeth, S.; Dey, K.; Banerjee, R. (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) represent a new field of rapidly growing chemical research that takes direct inspiration from diverse covalent bonds existing between atoms. The success of linking atoms in two and three dimensions to construct extended framework structures moved the chemistry of COFs beyond the structures to methodologies, highlighting the possibility of prospective applications. Although structure to property relation in COFs has led to fascinating properties, chemical stability, processability and scalability were some of the important challenges that needed to be overcome for their successful implementation. In this Perspective, we take a closer look at the growth of COFs from mere supramolecular structures to potential industrializable materials.